2019
DOI: 10.1016/j.asjsur.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting donor risk over two decades of single-center experience: More attention on the impact of overweight

Abstract: The overall complication rate was 20.9%. Overweight might be protective against morbidity in right hepatectomy and warrants further deliberation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…reported right lobe donation and overweight (BMI ≥ 25) were significant factors associated with donor morbidity 12 . Interestingly, they reported that being overweight was a paradoxical risk factor in right donor hepatectomy but not in left liver donors 12 . All of our grafts were right lobe therefore we cannot comment on the impact of BMI for left liver donation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…reported right lobe donation and overweight (BMI ≥ 25) were significant factors associated with donor morbidity 12 . Interestingly, they reported that being overweight was a paradoxical risk factor in right donor hepatectomy but not in left liver donors 12 . All of our grafts were right lobe therefore we cannot comment on the impact of BMI for left liver donation.…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, Ho et al. reported right lobe donation and overweight (BMI ≥ 25) were significant factors associated with donor morbidity 12 . Interestingly, they reported that being overweight was a paradoxical risk factor in right donor hepatectomy but not in left liver donors 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Based on their blood test result, age and BMI those individuals were considered in the study who have a perfect liver. In our recent work, it was described that ten years of a survey of 473 liver donors morbidity after liver hepatectomy 31 . This study describes that the average age of liver donors is not more than 30 years.…”
Section: Methodsmentioning
confidence: 99%
“…Live donor liver transplantation (LDLT) is the primary treatment option for endstage liver disease in countries that have organ shortages [1,2]. LDLT also provides a timely rescue for transplant candidates who may not survive long enough to receive liver transplants from deceased donors [3] However, live liver donation surgeries are not without risks and complications [4,5] Therefore, much effort has been devoted to expanding the maximal operability of live liver donations [6] and to reducing complications as much as is feasible.…”
Section: Introductionmentioning
confidence: 99%